Thiol-ene “Click” Reactions and Recent Applications in Polymer and Materials Synthesis: A First Update - Lowe, Andrew (R S C Publications, 2014)
This contribution serves as an update to a previous review (Polym. Chem. 2010, 1, 17–36) and highlights recent applications of thiol–ene ‘click’ chemistry as an efficient tool for both polymer/materials synthesis as well as modification. This current contribution covers examples from the literature published up to ca. mid 2013. It is not intended to be exhaustive but rather serves to highlight many of the new and exciting applications where researchers have applied thiol–ene chemistry in advanced macromolecular engineering and materials chemistry.